3D-architecture via self-assembly of Krebs-type polyoxometalate {[Na10(H2O)26][Sb2W20Zn2O70(H2O)6]}. (15th November 2018) - Ni, Lubin; Xu, Hongjie; Li, Huan; Zhao, Hongxia; Diao, Guowang
Graphical abstract: A 3D polyoxometalate frameworks are obtained from Zn 2+ /Na + -directed assembly of the {[Na10 (H2 O)26 ][Sb2 W20 Zn2 O70 (H2 O)6 ]}{Zn2 W2 } building block with new topology. Abstract: A novel Krebs -type polyoxometalate [Na10 (H2 O)26 ][Sb2 W20 Zn2 O70 (H2 O)6 ]Zn2 W2 (1) was fabricated from one-pot transformations of the trilacunary Keggin -type [B-α-SbW9 O33 ] 9− precursor, followed by Zn 2+ /Na + -assisted self-assembly of the Krebs -type polyanion. TheZn2 W2 polyanion was further self-assembled into 3D architecture with new topology by adjusting Na + cations. The compoundZn2 W2 (1) was fully characterized with a wide range of analytical methods, including single crystal/powder X-ray diffraction, thermogravimetric analysis (TGA) and various spectroscopic techniques (FT-IR, Raman, UV–vis). Electrochemical performance ofZn2 W2 polyanion was also investigated by cyclic voltammetry (CV) in sodium acetate buffer solution. Moreover, compoundZn2 W2 (1) is an effective catalyst for the oxidation of cyclohexanol with hydrogen peroxide.